Bridging technology adoption gaps in livestock sector in Ethiopia: A innovation system perspective - Ergano, Kebebe (Elsevier, 2019)
The failure of the majority of smallholder farmers in Ethiopia to take advantage of agricultural technologies and economic opportunities in the livestock sector remains an unresolved puzzle. This paper assesses the role of economic, social, political and organizational processes on technology adoption in smallholder livestock production systems based on innovation systems perspective. Functions of the innovation systems framework was used to assess the missing links in the dairy sector value chains. The results show that weak or missing innovation systems functions such as entrepreneurship, knowledge diffusion, market development, and policy advocacy mirror the low uptake of improved technologies in the livestock sector. Shortage of domestic suppliers of key technological inputs and services, weak input and output markets and weak interaction among value chain actors have been the major hindrances to livestock development. For example, there were no reliable sources of improved breeds of dairy heifers, veterinary supplies, quality semen, and equipment. The results suggest that technical knowledge and availability of economic opportunities alone may not be enough to stimulate the uptake of technologies and commercialization of dairy production. The peculiar nature of inputs, services, and output in the livestock sector requires innovative business models that can facilitate the coordination of knowledge, skills, inputs, services and output markets in livestock value chains.